Role of Magnesium and its mitochondrial transporter MRS2 in the modulation of drug-induced apoptosis leading to multidrug resistance phenotype - Merolle, Lucia <1986> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
Magnesium is an essential element for many biological processes crucial for cell life and proliferation. Growing evidences point out a role for this cation in the apoptotic process and in developing multi drug resistance (MDR) phenotype. The first part of this study aimed to highlight the involvement of the mitochondrial magnesium channel MRS2 in modulating drug-induced apoptosis. We generated an appropriate transgenic cellular system to regulate expression of MRS2 protein. The cells were then exposed to two different apoptotic agents commonly used in chemotherapy. The obtained results showed that cells overexpressing MRS2 channel are less responsiveness to pharmacological insults, looking more resistant to the induced apoptosis. Moreover, in normal condition, MRS2 overexpression induces higher magnesium uptake into isolated mitochondria respect to control cells correlating with an increment of total intracellular magnesium concentration. In the second part of this research we investigated whether magnesium intracellular content and compartmentalization could be used as a signature to discriminate MDR tumour cells from their sensitive counterparts. As MDR model we choose colon carcinoma cell line sensitive and resistant to doxorubicin. We exploited a standard-less approach providing a complete characterization of whole single-cells by combining X-Ray Fluorescence Microscopy , Atomic Force Microscopy and Scanning Transmission X-ray Microscopy. This method allows the quantification of the intracellular spatial distribution and total concentration of magnesium in whole dehydrated cells. The measurements, carried out in 27 single cells, revealed a different magnesium pattern for both concentration and distribution of the element in the two cellular strains. These results were then confirmed by quantifying the total amount of intracellular magnesium in a large populations of cells by using DCHQ5 probe and traditional fluorimetric technique.